A organização didática da Educação Física na educação de jovens e adultos no sistema público de ensino do município de Natal-RN - Barros, Joyce Mariana Alves (2016)
Understanding education in a reparative, equalizer and permanent way, as a right of every individual to the full exercise of their citizenship, this paper studies the Physical Education as a curriculum component of Basic Education in the EJA (Youth and Adult Education). This study aimed to discuss the didactic organization of Physical Education in EJA in the public school system of Natal-RN municipality, from the following specific objectives: a) identifying the educational context in which it operates Physical Education in EJA in Natal-RN and b) describe how the Physical Education teachers organize didactically discipline in EJA in Natal-RN municipality. Through the qualitative case study we investigated the pedagogical practice of teachers in that context. To this end, questionnaires were given to 15 teachers of the municipality education system in the period from 26 May to 25 July 2015, organized in three stages: 1) identification, 2) Practice of Physical Education in EJA and 3) Performance of Physical Education in EJA. It was concluded that the pedagogical practice of teachers investigated points referrals for Physical Education in EJA, such as: content, educational goals, evaluation, length of classes, teaching methodology, problems and prospects to act in this scenario, corroborating partly with curriculum guidelines of EJA in Brazil (2002) and Natal (2008), as the context of each teacher reveals a distinct identity. As inferences were identified absence of a theoretical framework that would direct the teaching work of Physical Education in EJA in the city of Natal-RN, many difficulties in the systematization of knowledge, lack of specific continued education formation of the teachers and, in most cases, no discussion on EJA in the initial training. On the latter, it is believed that the process of organizing the pedagogical practice of teachers is closely related to the initial and continued training, so it is urgent to revise strategies that promote the debate of Physical Education in EJA in Natal-RN municipality.